AKTIVITAS HUMAS PADA BIDANG PENGADUAN PEMERINTAH KOTA MAKASSAR DALAM MENINGKATAN CITRA PEMERINTAHAN - Audah Mannan; Mutmainnah Mutmainnah (Jurnal Komodifikasi, 2017)
The purpose of this study is to determine the public relations activities in the field of complaints of the city of Makassar in improving the image of government and to know the supporting factors and factors inhibiting public relations activities in the field of complaints pemassar municipality in improving the image of government. This research uses a rhetorical approach with a qualitative descriptive approach. Methods of data collection through observation, in-depth interviews, and library research. The data obtained then processed by qualitative descriptive analysis.The results showed that (1) Sub-section of public complaint is part of public relations. Public relations activity that complaints every day receive complaints either the print media, social media, online sms, telephone and direct complaints. Each complaint entered, followed up, called by the relevant SKPD responsible for the complaint. (2) Supporting factors in public relations activities in the field of complaints of press room, making post complaints and inhibiting factors in public relations activities in the field of complaints of facilities and infrastructure, human resources, coordination.The implication of the research is that the need to increase the socialization of the implementation of government service programs so that the public will not get bad service from SKPD which is in the embryo. Suggestions for the public relations section should be when someone conducts the research should provide direction or input on the activities undertaken by the public relations department. So that researchers are not confused and facilitate doing research.